Analisis Quietus Politik Terhadap Upaya Pemerintah Menangani Wabah Covid-19 Pasca Deklarasi Public Health Emergency Of International Concern (PHEIC) - Agus Pandoman (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2020)
This study examines what the Indonesian government has done after the declaration of the COVID-19 outbreak as PHEIC by WHO in terms of regulations and regulations. This research legal philosophical in the analysis of quietus politic theory concludes that the element of urgency in the determination of health emergencies is non-negotiable in its handling.